Pelatihan Aplikasi Jotform untuk Pembuatan Form Kuesioner dan Presensi - Ekasatya Aldila Afriansyah; Sukanto Sukandar Madio; Tina Sri Sumartini; Dian Mardiani; Cici Nurulhaq; Teni Sritresna; Reni Nuraeni (Jurnal Pekemas, 2020)
The problem of teacher weakness in using software applications to support the online learning process is the theme raised in this training. The solution offered from this training is the Jotform application. The purpose of this training activity is to introduce the Jotform application to teachers in Garut. The research implementation method consists of five stages, namely: introduction, socialization, training, practice, and monitoring. The object of this training activity is the teachers in the Garut region. The training was conducted in two sessions, namely: presentation of material and practice. The benefit of the Jotform application training is evident from the commitment of the training participants about the plan to implement the Jotform application in their learning class. The results of the evaluation of the implementation of this training indicate that this training is useful to support the teaching and learning process carried out in schools. The training method is able to improve the skills of teachers in using the Jotform application. The conclusion of this training is the knowledge in using the Jotform application for teachers so that it is hoped that in the future teachers in Garut will use the Jotform application in making attendance forms and questionnaires/assignments/quizzes